1979
DOI: 10.1128/jvi.32.3.895-904.1979
|View full text |Cite
|
Sign up to set email alerts
|

Cap and Internal Nucleotides of Reovirus mRNA Primers Are Incorporated into Influenza Viral Complementary RNA During Transcription In Vitro

Abstract: Reovirus mRNA's containing a 5′-terminal methylated cap structure (m 7 GpppG m ) were shown to be effective primers for influenza viral RNA transcription in vitro catalyzed by the influenza virion transcriptase. Priming activity required the presence of methyl groups in the cap since reovirus mRNA's with 5′-terminal GpppG were inactive as primers. Both the cap and internal nucleotides were physically transferred from radiolabeled reovirus mRNA to influenza viral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
23
0
2

Year Published

1981
1981
2014
2014

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(27 citation statements)
references
References 21 publications
2
23
0
2
Order By: Relevance
“…During transcription, multimeric viral polymerase interacts with the host polymerase II (Engelhardt et al, 2005). This interaction leads to the phenomenon called "cap-snatching", that is the removal of a cap from newly synthetized cellular mRNAs (Plotch et al, 1979;Bouloy et al, 1979;Bouloy et al, 1980;Krug, 1981). The PB2 subunit of viral polymerase is responsible for cap binding.…”
Section: Virus Adsorption Entry and Uncoatingmentioning
confidence: 99%
“…During transcription, multimeric viral polymerase interacts with the host polymerase II (Engelhardt et al, 2005). This interaction leads to the phenomenon called "cap-snatching", that is the removal of a cap from newly synthetized cellular mRNAs (Plotch et al, 1979;Bouloy et al, 1979;Bouloy et al, 1980;Krug, 1981). The PB2 subunit of viral polymerase is responsible for cap binding.…”
Section: Virus Adsorption Entry and Uncoatingmentioning
confidence: 99%
“…The structure of the 5Ј ends of THO virus mRNAs contrasts with that reported for all other viruses possessing a segmented, negative or ambisense, single-stranded RNA genome, including members of the Orthomyxoviridae (7,11,39), Arenaviridae (15,26,32,35), Bunyaviridae (3,5,13,16,20,29), and tenuiviruses (19,36), in which the 5Ј ends of viral mRNAs are heterogeneous in both length and sequence. For all of these viruses, it has been suggested that these additional nucleotides are generated by a cap snatching mechanism similar to that described for influenza A virus (4,30,31) and Bunyaviridae (29,42).…”
mentioning
confidence: 95%
“…These additional nucleotides, which are heterogeneous in sequence, are generated by a virus-encoded endonucleolytic activity that cleaves capped host-cell mRNAs (this mechanism is referred to as cap snatching) (31). The short capped fragments obtained from cellular mRNAs serve as primers for virus mRNA synthesis (4,30) and are elongated until the polymerase reaches a stretch of uridine residues, located at 17 to 22 nucleotides from the 5Ј ends of vRNAs, where transcription terminates and poly(A) is added to mRNA (37).…”
mentioning
confidence: 99%
“…Viral cap-dependent endonuclease polymerase cleaves small pieces of capped RNA around 10 to 13 nucleotides long from the 5'end (266). These primers initiate viral mRNA synthesis by DNA-dependent RNA polymerase (35). The viral RNA of influenza virus is bound to four viral proteins: NP protein and three P proteins (PB1, PB2 and PA) (159;326).…”
Section: Viral Rna Transcriptionmentioning
confidence: 99%
“…The border of internal exon is the 5' end splice site, and the 3' terminal exon is defined by the presence of cleavage and polyadenylation signal (178;270;293;355 35 binds the PyAg at the 3' splice site in many introns and the complex between SF1-U2AF at the 3' end of the intron and the U1 snRNP(+GSF) complex at the 5' splice site define the border of the intron (134;340;359).…”
Section: Rna Processing In the Cellular Machinerymentioning
confidence: 99%